Mechanical performance and durability of banana ﬁbre and coconut coir reinforced cement stabilized soil blocks - Thanushan, K.; Sathiparan, N. (Elsevier, 2022)
Agricultural waste disposal is said to be amongst one of the pressing environmental problems in many countries. Finding economical usage for this waste by incorporating it in a product is the approach often used to over- come associated environmental issues. Banana ﬁbre and coconut coir are major agricultural waste products in Sri Lanka and fewer amounts of these are converted into usable products. Manufacturing cement-stabilized soil blocks incorporating these waste materials is envisaged to reduce environmental impact. The present study fo- cused on the post-peak behaviour and durability of banana ﬁbre and coconut coir-strengthened cement-stabilized soil blocks. Banana ﬁbre and coconut coir reinforced cement-stabilized soil blocks were tested for compression, ﬂexural bending, water absorption, sorptivity, resistance against chemicals, wet-dry weathering and freeze-thaw weathering. The banana ﬁbre showed better post-peak behaviour in compression and coconut coir showed bet- ter post-peak behaviour in ﬂexural. Both ﬁbre reinforcements improved durability of cement block against acid attack, alkaline attack, wet-dry weathering and freeze-thaw weathering. Moreover, the specimen reinforced with coconut coir was found to exhibit better durability compared to the specimen reinforced with banana ﬁbres.
Keywords: Mortar; Recycling and reuse of materials; Fibre-reinforcement